Nilai Tukar Uang Konvensional dan Islam - Masna Ani Saputri; Imelda Deva Kirana; Aim Matus Sholihah; Puspita Andraini; Suci Hayati (Indo Publishing, 2025)
The exchange rate plays a crucial role in a country's economic stability, as it affects the competitiveness of exports and imports, capital flows, and monetary policy. This article presents a comparative review between the exchange rate mechanism in conventional economics based on market demand and supply and central bank policy (floating with fixed exchange rate) with the concept of sharf in Islamic economics that emphasizes the prohibition of usury, speculation, and real asset-based transactions. A descriptive qualitative research method with a desk study approach is used to analyze the latest academic literature and policy documents. The results of the analysis show that although both systems aim at exchange rate stability, Islamic economics offers a framework of fairness and transparency that limits extreme volatility through cash requirements, quantity equivalence (for similar currencies), and minimal intervention to maintain market balance. In contrast, the conventional system is more flexible in responding to global economic shocks but is vulnerable to speculation. These findings underline the importance of integrating sharia principles in the formulation of modern exchange rate policies to minimize uncertainty and support inclusive and sustainable economic growth.